The Complex Notion of the Capacity of a Child: Exploring the Term Capacity to Support the Meaningful Participation of Children in Family Law Proceedings - Emmie Henderson-Dekort; Hedwig van Bakel; Veronica Smits (Social Sciences, 2022)
This article aims to explore the concept of capacity as necessitated by provisions within the UNCRC such as articles 12 and 5, which emphasize participation, and the evolving capacities of children. In family law proceedings when children are involved, age and capacity are considered in order to assess if the meaningful participation of that child is accessible. There is limited literature to indicate how the capacity of a child is determined, especially for children who are younger than twelve. Rather than relying on age to gauge capacity levels, this paper provides a unique, interdisciplinary evaluation of capacity through a combination of both legal and child development perspectives. This article aims to use a critical lens and rights-based approach to analyze the current literature regarding the capacities of children and proposes that a deeper understanding of what capacity entails is required in order to ensure the meaningful participation of children.